(untitled) (Research, Society and Development, 2021)
Objective: The aim was to analyze the results of studies about the prevalence of Staphylococcus aureus and methicillin-resistant S. aureus among medical students. Methodology: A literature review was carried out from August to November 2020, being selected 19 articles from the Pubmed and “Biblioteca Virtual de Saúde” databases, using the descriptors “Methicillin-Resistant Staphylococcus aureus” and “Students, Medical”. Studies from the last 10 years that target medical students and samples collected by nasal swab were included. Results: Several studies have confirmed the hypothesis that, as students advanced in the academic years and, consequently, raised their exposure to hospital environments, colonization by methicillin-sensitive and resistant Staphylococcus aureus increased. However, some studies were divergent, not finding significant values ​​for this association. The prevalences found also varied according to the place and country surveyed. Conclusion: In general, the greater the exposure to hospital environments, the higher the rate of colonization of students by methicillin-resistant Staphylococcus aureus and Staphylococcus aureus.